A spectrophotometric method for the determination of Mefenamic acid in pharmaceutical dosage form - Mohammed Habib Rashid; Susan Wadie Sarsam; Najib Al-Sabea (College of Pharmacy / Mustansiriyah University, 2018)
A new, stable and accurate UV spectrophotometric method was introduced for the determination of Mefenamic acid content in pure pharmaceutical material and in tablet dosage form. The method was based on the formation of a metal complex between Mefenamic acid and Nickel (II), which showed to exhibit a maximum absorbance at 360 nm. The analytical results obtained for both the pure compound and the four samples from different pharmaceutical brands available in the Iraqi pharmaceutical market were validated statistically. A comparison of the results obtained for the brands under study has revealed that Mefenamic acid content of the different brands was in good agreement with the labeled values and was within the permitted allowed percentage limits according to the United States pharmacopeia.